Comparison of the optimal duration of clusters support in European Countries with different levels of innovation performance - Peter Burger (European Regional Science Association (ERSA), 2012)
In the last two decades the support of clusters has become a useful and frequently used tool for the improvement of country, and especially regional competitiveness in many countries. Nowadays, clusters are often supported from the public sources through cluster programs in multiple European countries, as well as in the USA, in Japan and South Korea, and in many other countries. The length of clusters support duration is various and usually depends on the conditions of the cluster program which provides this support. This paper deals with the influence of innovation performance of European countries, which is measured with the composite index called "Summary Innovation Index", on the optimal length of clusters support duration in these countries. The paper works with the assumption that the countries with higher levels of innovation performance, where generally powerful and well-established clusters are active, tend to consider shorter periods of time as an optimal length of support duration from public sources in comparison with the countries having lower levels of innovation performance, where clusters do not have such a long tradition and where their economical background is on lower levels. In order to be able to accept or to reject this hypothesis, a primary research with the participation of 122 different clusters from 24 European countries was carried out. The clusters themselves, they consider the problem of optimal length of clusters support duration from public sources as very important and moreover, some clusters answered in the survey that they do not consider the lack of financial resources, but the short length of support duration to be the important problem of their funding. Considering that in the long term Slovakia belongs to the countries with the lowest support of clusters in the European Union, an another goal of the paper and the research itself has been the question what length of clusters support duration from public sources consider Slovak clusters as optimal and if the opinions of Slovak clusters on this optimal length of support duration from the public sources are different from the point of view of clusters in the countries, where clusters have a strong position and are supported simultaneously on the national, regional, and local levels.
Keywords: R12; R58; 330; clusters; optimal length of clusters support duration; cluster programs